2012
DOI: 10.1111/j.1469-8137.2012.04310.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid interacts antagonistically with classical defense pathways in rice–migratory nematode interaction

Abstract: SummaryStudies involving plant-nematode interactions provide an opportunity to unravel plant defense signaling in root tissues. In this study, we have characterized the roles of salicylate (SA), jasmonate (JA), ethylene (ET) and abscisic acid (ABA) in plant defense against the migratory nematode Hirschmanniella oryzae in the monocot model plant rice (Oryza sativa).Experiments with exogenous hormone applications, biosynthesis inhibition and mutant/ transgenic lines were executed to test the effect on H. oryzae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 88 publications
3
108
1
4
Order By: Relevance
“…In addition, Spodoptera littoralis and Spodoptera exigua larvae grew better on Arabidopsis ABA2-1-deficient mutants and ABA-deficient tomato plants, respectively (Thaler and Bostock, 2004;Bodenhausen and Reymond, 2007). The application of exogenous ABA and the balance of ABA and SA/JA/ethylene affected rice's defenses against Hirschmanniella oryzae (Nahar et al, 2012). Such findings are consistent with a significant role of ABA in regulating plant-herbivore interactions; however, the mechanisms of ABA's role, known as the typical drought-related hormone, in defense against herbivores remain to be understood in detail.…”
Section: Aba-ja Cross Talk In Herbivory and Pathogen Resistancementioning
confidence: 99%
“…In addition, Spodoptera littoralis and Spodoptera exigua larvae grew better on Arabidopsis ABA2-1-deficient mutants and ABA-deficient tomato plants, respectively (Thaler and Bostock, 2004;Bodenhausen and Reymond, 2007). The application of exogenous ABA and the balance of ABA and SA/JA/ethylene affected rice's defenses against Hirschmanniella oryzae (Nahar et al, 2012). Such findings are consistent with a significant role of ABA in regulating plant-herbivore interactions; however, the mechanisms of ABA's role, known as the typical drought-related hormone, in defense against herbivores remain to be understood in detail.…”
Section: Aba-ja Cross Talk In Herbivory and Pathogen Resistancementioning
confidence: 99%
“…7A). While the function of jasmonic acid and abscisic acid signaling in directing plant response to cyst nematodes is not fully understood (Kammerhofer et al, 2015), it has been recently demonstrated that these pathways regulate defense responses and basal immunity against sedentary and migratory nematodes (Nahar et al, 2011(Nahar et al, , 2012Ozalvo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The JA pathway is a key player in systemic induced defense against RKN in tomato (Cooper et al 2005), and SA actions downstream in initiating Mi-1-mediated resistance to both aphids and nematodes (Branch et al 2004;Li et al 2006). However, the ABA pathway antagonizes the SA/JAdependent core defense system, leading to enhanced susceptibility to root-parasitic nematodes (Hirschmanniella oryzae) (Nahar et al 2011(Nahar et al , 2012. The importance of the JA pathway to nematode resistance has also been reported in rice (Frey et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 μg RNA was treated with DNase-I and used for first-strand cDNA synthesis using Maloney murine leukemia virus reverse transcriptase (TaKaRa, Dalian, China) according to the manufacturer's protocol and primed by Oligo18 (Nahar et al 2012). RNA quality was measured by separation in 1.0 % agarose gels, staining with ethidium bromide and observing under UV.…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%